Workforce-, classroom- and program- level predictors of quality in infant and toddler programs: How subsidized programs compare with other center-based programs. (December 2020) - Slicker, Gerilyn; Tang, Jing; Kelly, Cara L.
Highlights: The EHS workforce had more education and training than subsidized centers. The subsidized workforce was paid less than EHS and non-publicly funded centers. Subsidized centers had larger ratios than Public ECE but lower group size than EHS. EHS and Public ECE offered more family ancillary services than subsidized centers. EHS offered more supports and coaching for its workforce than subsidized centers. Abstract: Finding affordable child care, especially for infants and toddlers, is incredibly challenging for low-income families. Child care subsidies can assist low-income working families with accessing child care and by expanding slots available for the youngest children. However, little is known about how workforce-, classroom-, and program-level predictors of quality vary across child care programs that serve low-income infants and toddlers. The current study fills a critical gap in the existing literature by comparing regulatable features of infant and toddler programs in moderate- and high- poverty areas that serve children paid for with child care subsidies with other publicly and non-publicly funded programs using nationally representative data from the 2012 National Survey of Early Care and Education (n = 1091). Our results show that while programs serving children receiving child care subsidies tend to fall short of other publicly funded programs (i.e., Early Head Start) as it relates to the program-level indicators of quality, programs that serve children receiving subsidies typically have smaller group sizes than Early Head Start. In addition, though they tend to be less educated and are compensated at lower rates, the workforce in subsidized programs are more likely to report that they work to help children and families. Our findings suggest specific features of the workforce, classrooms, and programs that are regulated by federal, state, and local funding streams and policies that could be targeted to better support access for quality infant and toddler care, particularly for low-income families.